MODEL PENDIDIKAN KEDISIPLINAN PESANTREN MODERN UMMUL QURO AL – ISLAMI - agus ali; Neng Ikrimah Aziz Zamakhsyari (Al-Mubin, 2018)
The pesantren has existed in the community for six centuries (starting in the 15th century) and since its inception, the pesantren has offered education to those who are still illiterate. Besides that, Pesantren has also been the only educational institution owned by the indigenous community that has made a huge contribution in shaping literacy and cultural literacy. Pesantren as a future-oriented educational institution certainly has goals, curriculum, vision and mission in an effort to form a more civilized nation. Pesantren is one of the educational institutions in Indonesia, which is increasingly rapidly adjusting to the development of the current era, even some of them have experienced a transformation of the educational model in it. Islamic boarding schools which were inhabited by students as students who initially used the salafi method, then migrated to the kholafi method or often referred to as modern boarding schools. Disciplinary education is an important element in realizing a generation of Islam that excels in achievement as well as devotion to Allah SWT. Modern pesantren applies discipline to all students so that later they become habits in daily life. This paper discusses the model of disciplinary education and the efforts of pesantren in upholding it. The approach used in this study is qualitative with a survey method. Data were analyzed from materials collected based on field research and literature. This study found that the model of disciplinary education in the Modern Islamic Boarding School of Umm al-Quro Al-Islami is through the process of habituation, giving advice and reprimand as well as giving awards and punishment